The Early Stage Adjacent Disc Degeneration after Percutaneous Vertebroplasty and Kyphoplasty in The Treatment of Osteoporotic VCFs - Qian, Jun; Yang, Huilin; Jing, Juehua; Zhao, Hong; Ni, Li; Tian, Dasheng; Wang, Zhengfei (PLOS ONE, 2012)
Background The purpose of this paper is to determine the early incidence of disc de- generation adjacent to the vertebral body of osteoporotic fracture treated with percutaneous vertebroplasty or balloon kyphoplasty and whether adjacent disc degeneration is accelerated by this two procedures. Methods 182 patients with painful vertebral compression fractures were treated. A total of 97 patients were enrolled in this prospective study. 97 patients with a mean age of 65.3 years were classified into control group and surgical treatment group of non-random. 35 patients were in contol group and 62 patients who were performed percutaneous vertebroplasty or balloon kyphoplasty in treatment group. X-ray and Magnetic resonance imaging were done at the first and final visit. The grade of disc degeneration above the fractured vertebral was confirmed by evaluation of bony oedema in the fat suppressed sequences and T2-weighted image of magnetic resonance imaging. The height of degenerative disc was measured on X-ray film. Results All patients were followed up two years after the first visit and the follow-up rate was 90.7% (88/97). The incidence of degeneration of adjacent disc above the fractured vertebral was 29.0% (9/31) in control group and 52.6% (30/57) in treatment group. It presented a statistically significant difference between two groups about the incidence of adjacent disc degeneration (P = 0.033). The percentage of adjacent disc height reduction in control group was 13.5% and 17.6% in treatment group. Statistically significant difference of VAS score and ODI was not found between the first evaluation postoperatively and the final follow-up in treatment group (P>0.05). Conclusions Disc degeneration adjacent to the fractured vertebral is accelerated by VP and BK procedures in the early stage, but clinical outcomes has not been weakened even in the presence of accelerated disc degeneration.